Fire Evaluation on Thermal Oxidizer (TOX) at XY Company with Fishbone Approach - Izagy Rif’at, Bayu; Aprilia Dewinta, Keysa; Ardhana, Muhammad Jaggu; Hifdzia, Naila; akbar ramadhan, raihan (Sahabat Publikasi, 2024)
On April 9, 2020, Thermal Oxidizer (TOX) at PT. XY burned. Its function is to control exhaust emissions by burning harmful organic compounds. In this case, the Waste Heat Recovery Unit (WHRU) located above the TOX combustion chamber failed. Gas Turbine Generators (GTG) failed. This study uses a fishbone diagram approach to identify the cause of the fire. Maintenance policies, machine errors, human error, extreme environmental conditions, and inadequate operational procedures are some of the causes. The results of the analysis show that improving workers' operational skills, regular equipment inspections, and improving safety management systems are essential. These results provide practical advice to improve operational safety and prevent similar incidents in the future